2016
DOI: 10.1186/s12911-016-0334-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinician time used for decision making: a best case workflow study using cardiovascular risk assessments and Ask Mayo Expert algorithmic care process models

Abstract: BackgroundRisk calculation is increasingly used in lipid management, congestive heart failure, and atrial fibrillation. The risk scores are then used for decisions about statin use, anticoagulation, and implantable defibrillator use. Calculating risks for patients and making decisions based on these risks is often done at the point of care and is an additional time burden for clinicians that can be decreased by automating the tasks and using clinical decision-making support.MethodsUsing Morae Recorder software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Physicians recommended shortening and reorganizing the alert content for clarity and embedding a link to an order set specific for FH so as to reduce the number of clicks. Physicians also recommended including a link to AskMayoExpert, a Mayo Clinic knowledge resource with a topic module dedicated to FH that provides information on clinical presentation, diagnostic criteria and management [ 44 ]. AskMayoExpert also has links to additional knowledge modules, thereby enabling providers to access a number of relevant topics without workflow disruption [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians recommended shortening and reorganizing the alert content for clarity and embedding a link to an order set specific for FH so as to reduce the number of clicks. Physicians also recommended including a link to AskMayoExpert, a Mayo Clinic knowledge resource with a topic module dedicated to FH that provides information on clinical presentation, diagnostic criteria and management [ 44 ]. AskMayoExpert also has links to additional knowledge modules, thereby enabling providers to access a number of relevant topics without workflow disruption [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only 10% of providers indicated that they currently use AME for PAD risk modification. Although AME provides knowledge-based care process models, 17 71% of respondents perceived greater potential benefit of individualized risk score calculators and guideline-recommended strategies at the point of care. Importantly, care process models are not individualized for use at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…Initial questions assessed provider demographic characteristics, including role, primary work area, years in practice, and the number of patients seen with PAD. Subsequent questions investigated how helpful providers considered the current version of Ask Mayo Expert (AME), a Mayo Clinic online knowledge-based care process model 17 for secondary prevention in patients with PAD as well as provider comfort level in caring for patients with PAD. The final questions investigated provider opinions on the potential helpfulness of an advanced CDS system that would automatically display secondary prevention strategies for patients with PAD and an automated risk score for mortality for these patients at the point of care.…”
Section: Methodsmentioning
confidence: 99%
“…Automatically calculated risk scores can be used successfully in population health management. 24 Despite these barriers, an innovative workflow was introduced within the electronic health record which resulted in surpassing our aim of a 10% increase in ASCVD risk score assessment within 12 months. Physician’s barriers to the acceptance of ASCVD risk assessment included: lack of electronic chart alerts and lack of extra time needed to complete the ASCVD risk score assessment during the limited clinic visit while addressing multiple chronic diseases.…”
Section: Resultsmentioning
confidence: 99%